2005
DOI: 10.1055/s-2005-836411
|View full text |Cite
|
Sign up to set email alerts
|

Konventionelle oder laparoskopische Operation der perforierten Appendizitis - Eine vergleichende Studie

Abstract: Laparoscopic appendectomy is a safe procedure for the treatment of complicated appendicitis with a significantly decreased complication rate and shorter postoperative stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
1
1
0
2
Order By: Relevance
“…A relatively small number of cases were done during the study time period and this is part of the surgeons' learning curve where the complications and conversions tend to be relatively higher. A conversion rate of up to 9% has been reported in busy high volume hospitals with laparoscopic appendicectomy [24,25]. Complications included spinal headache which was 2.6% in all the laparoscopic procedures which was comparable to that found in other studies.…”
Section: Discussionsupporting
confidence: 68%
“…A relatively small number of cases were done during the study time period and this is part of the surgeons' learning curve where the complications and conversions tend to be relatively higher. A conversion rate of up to 9% has been reported in busy high volume hospitals with laparoscopic appendicectomy [24,25]. Complications included spinal headache which was 2.6% in all the laparoscopic procedures which was comparable to that found in other studies.…”
Section: Discussionsupporting
confidence: 68%
“…[151][152][153][154][155][156] However, the conversion rate then increases up to 47%. Kapischke et al 157 found a conversion rate of only 2.5%, indicating that the experience of the surgeon plays an important role in this discussion. Operative success in complicated appendicitis depends on the following: diligent intraabdominal lavage (especially the pouch of Douglas, subhepatic and subphrenic spaces on the right side), placement of the drain in the lowest point in Douglas's space for both drainage (Easyflow) and postoperative lavage, and safe removal of the appendix.…”
Section: Appendectomymentioning
confidence: 89%
“…Auch diese sieben Appendices wiesen im präoperativen Ultraschall alle Zeichen einer akuten Appendizitis ohne sicheren Nachweis einer Perforation auf. Die SPA ließ sich auch in diesen Fällen problemlos durchführen, wie in der Literatur im Falle der LA mehrfach beschrieben wird [16,18,38]. Einschränkend ist anzumerken, dass diese sieben perforierten Appendices makroskopisch eine beginnende Perforation aufwiesen.…”
Section: Perforierte Appendizitisunclassified